Analisis Faktor Produksi dan Pendapatan Usahatani Padi Sistem Salibu di Desa Sabaran Kecamatan Jawai Selatan Kabupaten Sambas - Artiandi, Muhammad; Suyatno, Adi; Kurniati, Dewi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Population growth that continues to increase, if not balanced by an increasing rice production, will lead to a shortage of rice supply in Indonesia. The